2022
DOI: 10.5946/ce.2021.228
|View full text |Cite
|
Sign up to set email alerts
|

Does computer-aided diagnostic endoscopy improve the detection of commonly missed polyps? A meta-analysis

Abstract: Background/Aims: Colonoscopy is the gold standard diagnostic method for colorectal neoplasia, allowing detection and resection of adenomatous polyps; however, significant proportions of adenomas are missed. Computer-aided detection (CADe) systems in endoscopy are currently available to help identify lesions. Diminutive (≤5 mm) and nonpedunculated polyps are most commonly missed. This meta-analysis aimed to assess whether CADe systems can improve the real-time detection of these commonly missed lesions.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…2 There are multiple factors contributing to successful adenoma detection. Technological improvements such as high-definition colonoscopy and imaging technologies including computer aided diagnostic endoscopy (CADe) improve the detection of lesions 3 and endoscopic adjuncts such as EndoCuff improve the exposure of lesions with a demonstrable improvement of ADR. 4,5 The visual patterns of an endoscopist, that is, what the endoscopist is looking at during luminal examination of the colon, is an interesting area of endoscopy with an evolving evidence base.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 There are multiple factors contributing to successful adenoma detection. Technological improvements such as high-definition colonoscopy and imaging technologies including computer aided diagnostic endoscopy (CADe) improve the detection of lesions 3 and endoscopic adjuncts such as EndoCuff improve the exposure of lesions with a demonstrable improvement of ADR. 4,5 The visual patterns of an endoscopist, that is, what the endoscopist is looking at during luminal examination of the colon, is an interesting area of endoscopy with an evolving evidence base.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple factors contributing to successful adenoma detection. Technological improvements such as high‐definition colonoscopy and imaging technologies including computer aided diagnostic endoscopy (CADe) improve the detection of lesions 3 and endoscopic adjuncts such as EndoCuff improve the exposure of lesions with a demonstrable improvement of ADR 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…They all show a more or less significant increase in detection of small adenomas. The same results are summarized over and over again in no less than 16 meta-analyses 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 , plus a protocol for a further one 36 , as well as a meta-analysis of some of these meta-analyses 37 !…”
mentioning
confidence: 96%
“…The first studies using approved AI systems unanimously demonstrated an increase of adenoma detection rate (ADR), number of adenomas per patient as well as a reduction in adenoma and neoplasia miss rate that was mainly achieved due to detection of small and diminutive polyps. [2][3][4][5] In some studies, the high number of additional polyps detected with AI could at least in parts be attributed to a low baseline ADR in the control groups. 6 In their paper, Silvia Pecere and colleagues performed an analysis of published data.…”
mentioning
confidence: 99%
“…The first studies using approved AI systems unanimously demonstrated an increase of adenoma detection rate (ADR), number of adenomas per patient as well as a reduction in adenoma and neoplasia miss rate that was mainly achieved due to detection of small and diminutive polyps 2–5 …”
mentioning
confidence: 99%